2020
DOI: 10.3892/or.2020.7469
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑29c‑3p acts as a tumor suppressor gene and inhibits tumor progression in hepatocellular carcinoma by targeting TRIM31

Abstract: Aberrant expression of microRNAs (miRNAs) has been widely reported in many malignant tumors, and dysregulated miRNAs play an important role in the malignant progression of tumors. It has been reported that miR-29c-3p expression is dysregulated in tumors and promotes the development of tumors, especially in hepatocellular carcinoma (HCC). However, the specific mechanism of miR-29c-3p in HCC is not clear. The present study demonstrated that miR-29c-3p was expressed at low levels in HCC patients and cell lines an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…MiRNAs are widely involved in the regulation of various functional genes. Functional disorders of miRNAs are often related to the development and metastasis of tumor cells (21). Recent studies have also found that miR-29c-3p is associated with a variety of malignancies, showing abnormal expression in cancer cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are widely involved in the regulation of various functional genes. Functional disorders of miRNAs are often related to the development and metastasis of tumor cells (21). Recent studies have also found that miR-29c-3p is associated with a variety of malignancies, showing abnormal expression in cancer cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-424-5p acts as a tumor suppressor by targeting TRIM29 [ 45 ]. MiR-29c-3p down-regulates TRIM31 expression [ 53 ]. MiR-4417 down-regulates TRIM35 [ 54 ].…”
Section: Expression Pattern and Biological Functions Of Trim Proteins...mentioning
confidence: 99%
“…Additionally, studies have confirmed that low expression of miR-29b-3p, miR-29c-3p is associated with tumor growth, multiple pathological features, and shorter OS (32). Several HCC-related reports have noted that the overexpression of miR-29b-3p, miR-29c-3p significantly inhibits the proliferation, apoptosis, migration, and tumor growth of HCC cells in vivo (33,34).…”
Section: Discussionmentioning
confidence: 86%